PEMERIKSAAN JENIS DAN KADAR ZAT PEWARNA BUATAN PADA PERMEN LOLIPOP BERMEREK DAN TIDAK BERMEREK YANG BEREDAR DI KOTA MEDAN TAHUN 2012 - Fransisca Mariana Batubara; wirsal hasan; Devi Nuraini Santi (Lingkungan dan Kesehatan Kerja, 2013)
Laboratory Analysis of the types and rate artificial dyes lollipop candy branded and unbranded around in Medan city. Lolipop candy is a popular product of snack to eat with variously types, have a prominently colors, that many people like it. In order to attract the consumer mostly the dyes substance as used to the product known as restricted formula due to the product may cause a dangerous impact over the human health. The objective study is to determine the sort and grade of artificial dyes rate on the lollipop branded candy and lollipop non-branded candy on Medan City for 2012. To view whether the uses of the artificial dyes on lollipop candy fulfilling the requirement for health. The method used study in survey research with descriptive one. The sample taken from Petisah Market, Thamrin Plaza, Medan Fair Plaza, Palladium Plaza, and also from Supermarket operation on this city, bring it to laboratory for examination. The result showed that from 7 types of the market lollipop candy existed on market and in examination found that it contained an artificial dyes as not permitted that is Ponceau 3R and another 7 samples of lollipop non-branded candy in examination, 1 samples containing artificial dyes not permitted that is Ponceau 3R. The rate noted on 7 samples of lollipop branded candy found at least 3 samples not fulfilling the requirement that is 441 mg/kg, 450 mg/kg, 451 mg/kg and 1 sample of  lollipop non-branded candy not seemly fulfilling the requirement because used an artificial dyes not permitted. It is suggested to Balai POM is seriously to make a strictly control and supervision into the uses of additional substances for producing foods. Keywords : lollipop candy, artificial dyes, the rate